The impact of CEO tenure on employees’ salary: evidence from China - Jing Liu (Humanities & Social Sciences Communications)
Abstract Based on A-share listed firms in China from 2012 to 2019, ordinary least squares regression and quantile regression methods are used to analyze CEO tenure on the salary policy of employees quantitatively. Empirical results suggest that in the early stage of CEO tenure, the CEO tends to increase both the salary and the employee pay-performance sensitivity to motivate employees, and the effect can be more significant for employees with stronger bargaining power in the labor market. Further analysis finds that the effect of CEO tenure mainly exists in the firms whose CEO is promoted within the firm. In addition, the negative effect of CEO tenure on employee pay-performance sensitivity only exists in firms with smaller staff scales. The research in this paper not only enriches the factors that influence employees’ salaries but also contributes to a more comprehensive understanding of corporate politics. This study provides theoretical guidance for employees’ salary policies and helps formulate motivation strategies for enterprises.